PERSEPSI SISWA KELAS XII SMA NEGERI TERHADAP LEMBAGA BIMBINGAN BELAJAR (Journal of Biology Education, 2012)
Pelaksanaan ujian nasional dan ujian masuk perguruan tinggi merupakan bentuk kompetisi untuk siswa kelas dua belas. Lembaga bimbingan belajar memberikan penawaran yang menarik dalam mempersiapkan siswa untuk ujian nasional dan ujian masuk perguruan tinggi. Penelitian ini bertujuan untuk menggambarkan persepsi siswa kelas dua belas terhadap lembaga bimbingan belajar di Semarang. Ini merupakan penelitian deskriptif dengan mengambil sampel dari 177 siswa kelas dua belas dari lima SMA negeri di Semarang. Siswa belajar untuk mengikuti bimbingandi lembaga les GO, Exains, Neutron dan Primagama. Variabel penelitian ini adalah persepsi siswa terhadap guru (tentor), fasilitas, media pembelajaran, bahan ajar, metode  pengajaran, evaluasi program, waktu pelaksanaan dan biaya les, terutama mata pelajaranbiology. Hasil penelitian adalah, nilai persepsi siswa terhadap staf pengajar(tentor), fasilitas, media pembelajaran, bahan pelajaran, metode mengajar,evaluasi program, waktu pelaksanaan dan biaya les dalam mata pelajaran Biologi antara 20% -86,70% setiap aspect. Simpulannya persepsi siswa terhadap lembaga-lembaga bimbingan belajar di Semarang baik. Oleh karena itu, guru dan sekolah harus dapat menanggapi persepsi siswa dari les dengan menerapkannya di sekolah.Implementation of the national exams and college entrance exams is a form of competition for the twelfth grade students. Institutions tutoring provides an attractive offer in preparingstudents for national exams and college entrance exams. This study aims to describe the perceptions of twelfth grade students of senior high school of the institute tutoring in Semarang. This study is a descriptive research by taking a sample of 177 twelfth grade students from five of state senior high schools in Semarang. Students learn to follow the  guidance in the institute tutoring GO, Exains, Neutron and Primagama. The variables of this study is the perception of students to wards teachers (tentor), facilities, instructional media, learning materials, teaching methods, program  evaluation, implementation time and cost tutoring subjects, especially biology. These results indicate the perception scores of students to teaching staff (tentor), facilities, instructional media, learning materials, teaching methods, program evaluation, implementation time and cost tutoring biology in particular subjects is 20% - 86.70% every aspect. Based on the results of the study concluded that student’s  perceptions is well to the institutions tutoring in the Semarang. There fore, teachers and schools should be able to respondto student’s perceptions of tutoring by applying it in schools.